Hubungan Antara Harga Diri dengan Interaksi Sosial pada Orang dengan HIV AIDS di Yayasan Lantera Minangkabau Support - Yudhi Aulia; Ira Erwina; Alfitri (NERS Jurnal Keperawatan, 2014)
PLWHA (People with HIV AIDS) is not just having problems physically or biologically, but also experience psychological problems, social and spiritual. When a person has been diagnosed with the HIV virus in the psychosocial assessment of PLWHA will withdraw from the environment. Disruption of self-esteem affect communication PLWHA who are part of the process of social interaction. The purpose of this research is to know the extent of fatherly pride relationship with social interactions in people with HIV-AIDS. The research was conducted at Yayasan Lantera Minangkabau Support Padang from April to May 2013. This research is correlational cross-sectional approach. Total sample in this study of 45 PLWHA using total sampling technique. Collecting data using a questionnaire using a Likert scale for the variable self-esteem and social interaction. Univariate data analysis done for the bivariate frequency distribution and performed with Spearman's test. The results showed as much as 91.4% of PLWHA have positive self-esteem and 64.4% of PLWHA with good social interaction. There was no significant association between self-esteem and social interaction. The result is expected to be information and increase knowledge in promoting nursing care for PLWHA.